Implementasi Pengenalan Lapangan Persekolahan (PLP) I, Minat Menagajar terhadap Kesiapan Menjadi Guru bagi Mahasiswa - Hevitria; Said Akhmad Maulana; Nurwandi (UNIB Press, 2024)
The purpose of this research is to determine the implementation of the introduction to the field of learning (PLP) I in schools, towards teaching readiness to become teachers for students. Introduction to School Fields (PLP) I is a Faculty activity that is routinely held for 10 days in February. This activity is an observation process while at school, the observations made are about the condition of the school, the learning process and the culture at school. The population of this research is students from the Faculty of Teacher Training and Education with four study programs: PGSD, PJKR, PMTK with PBI funds with a total of 344 students and consisting of 33 schools in Pangkalpinang. Data collection used Google forms and KHS obtained from the administration of the Faculty of Teacher Training and Education, Unmuh Babel. The data analysis technique used in this research uses multiple linear regression analysis. The results of this research indicate that there is a positive influence from the implementation of PLP I on the teaching readiness variable for FKIP students. The Kolmogorov test results show that 0.209 > 0.05, which means that the residual data is normally distributed. The results of the simple linear regression test show that 0.000 < 0.05. This shows that between the independent variable and the dependent variable there is a linear relationship.